2015
DOI: 10.1186/1476-069x-14-11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2011 heat wave on mortality and emergency department visits in Houston, Texas

Abstract: BackgroundHeat waves have been linked to increased risk of mortality and morbidity, and are projected to increase in frequency and intensity in a changing climate. Houston and other areas in Texas experienced an exceptional heat wave in the summer of 2011 producing the hottest August on record. This study aims to assess the health-related impact of this heat wave.MethodsDistributed lag models were used to estimate associations between the 2011 heat wave and all-cause mortality and emergency department (ED) vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 23 publications
3
43
2
2
Order By: Relevance
“…While some areas experience more intense heat than others, this is a widespread issue; for example, cities all across the United States are projected to see an increase in the number of extremely hot days over this century [3]. Extreme heat events of the past few decades have created major disturbances including infrastructure damage, economic loss, and human illness and death [4][5][6][7][8], the latter two of which have been shown to disproportionately impact vulnerable populations, such as the elderly, low-income, and those with pre-existing health conditions [9][10][11][12]. Considering the current and expected future influence of extreme heat on public health, social welfare and urban resilience, local decision makers have a duty to identify and mitigate sources of excess heat within their cities.…”
Section: Introductionmentioning
confidence: 99%
“…While some areas experience more intense heat than others, this is a widespread issue; for example, cities all across the United States are projected to see an increase in the number of extremely hot days over this century [3]. Extreme heat events of the past few decades have created major disturbances including infrastructure damage, economic loss, and human illness and death [4][5][6][7][8], the latter two of which have been shown to disproportionately impact vulnerable populations, such as the elderly, low-income, and those with pre-existing health conditions [9][10][11][12]. Considering the current and expected future influence of extreme heat on public health, social welfare and urban resilience, local decision makers have a duty to identify and mitigate sources of excess heat within their cities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found an association between high ambient temperature (specifically during extreme heat waves) and elderly health outcomes, e.g. increased mortality rates, ED visits and hospital admissions [6,7]. Thus, elderly patients are more vulnerable to dehydration and insensible loss, especially during high temperature periods even when they stay indoors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Insgesamt stammen viele Studien zu Hitzewellen oder Hitzebedingten gesundheitlichen Problemen aus Gebieten mit tropischem oder subtropischem Klima: Korea [14], Vietnam [15], Texas/ USA [16], Spanien und Italien [17,18] sowie Australien [19,20]. Wenige Studien existieren zur Hitze-bedingten Morbidität und Mortalität in gemäßigtem Klima [4,[21][22][23].…”
Section: Introductionunclassified